Effects of Radiation on Materials: 21st International Symposium 2004
DOI: 10.1520/stp11259s
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation Induced Vacancy-Cu Aggregations in Fe-Cu Model Alloys of Reactor Pressure Vessel Steels Studied by Positron Annihilation

Abstract: Fe-Cu model alloys (0, 0.05, 0.15, 0.30 and 1.00 wt.%Cu) of Nuclear Reactor Pressure Vessel Steels irradiated by fast neutrons (8.3×1018 n/cm2) at about 100°C are studied by positron annihilation spectroscopy, positron lifetime and coincidence Doppler roadening, in order to analyze the irradiation-induced vacancy-Cu aggregation. We have observed nanovoids (vacancy clusters) whose inner surfaces are covered by Cu atoms in not only high and medium Cu (0.15–1.0 wt.%) alloys but also low Cu (0.05 wt.%) alloys. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Vacancy components such as vacancies and microvoids can be examined by using PA techniques. Several studies using positron lifetime measurements showed that microvoids containing more than 10 vacancies were formed in binary or ternary model alloys [105,106]. A recent study showed that only vacancies and divacancies existed in irradiated Fe-Mn-Ni and Fe-Mn-Ni-Cu model alloys, while vacancy clusters containing more than 10 vacancies were formed in Fe-Cu alloys [104].…”
Section: Matrix Damagementioning
confidence: 99%
See 1 more Smart Citation
“…Vacancy components such as vacancies and microvoids can be examined by using PA techniques. Several studies using positron lifetime measurements showed that microvoids containing more than 10 vacancies were formed in binary or ternary model alloys [105,106]. A recent study showed that only vacancies and divacancies existed in irradiated Fe-Mn-Ni and Fe-Mn-Ni-Cu model alloys, while vacancy clusters containing more than 10 vacancies were formed in Fe-Cu alloys [104].…”
Section: Matrix Damagementioning
confidence: 99%
“…However, it is necessary to carefully consider interactions between point defects and solute atoms. It is evident that Cu-rich clusters in high-Cu model alloys are formed in a manner that Cu atoms cover the inner surface of microvoids [84,105]. Some fraction of vacancies must be assumed for explaining SANS data (mass density of the clusters) of the clusters formed in commercial steels [3].…”
Section: Matrix Damagementioning
confidence: 99%